Sustaining and strengthening higher education in International Islamic University Malaysia : the role of quality assurance exercises - Abdul Rahman, Shukran; Zubairi, Ainol Madziah (Penerbit Universiti Sains Malaysia, 2011)
The focus of the current quality assurance frame,Yorks appears to fit well with the structure of the efforts by many higher learning institutions including higher learning institutions in Malaysia. The delivery of academic services designed according to the set standard by university academic systems helps promote a university's quality initiatives. It is essential in strengthening the roles of an higher learning institution, and shaping its direction to face the increasingly challenging demands towards higher learning institution. The exercise of quality assurance helps a higher learning institution to substantiate, and in turn strategically strengthen its role as a higher learning institution especially in managing its functions in carrying out the university's mission and attaining its vision. In this regard, many higher learning institutions have adopted the many available quality-related systems including the ranking and rating systems. There are a number of pertinent impacts and issues which are associated with this exercise. This chapter presents an evaluation of institutional level study of the International Islamic University Malaysia (IIUM), which has been participating in, and benefiting from, a number of quality assurance related systems